1957
DOI: 10.1121/1.1909101
|View full text |Cite
|
Sign up to set email alerts
|

Sound Velocity and Attenuation in Bubbly Mixtures Measured in Standing Wave Tubes

Abstract: Experimental measurements of sound velocity and attenuation constant in a mixture of air bubbles in fresh water, using a standing wave tube, are described. Bubble sizes in the mixtures were controlled between about 0.08- and 0.26-in. diameter, concentrations ranged from 0.03 to 1%, and applied frequencies from 60 to 20 000 cps. Bubbles in each mixture were of a single uniform size except for one series of experiments in which mixtures of bubbles of two discrete sizes were used. Attenuation constants were obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
78
1

Year Published

1966
1966
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 222 publications
(91 citation statements)
references
References 0 publications
12
78
1
Order By: Relevance
“…Figures 1 and 8 of Commander and Prosperetti (1989) show the dispersion and phase velocity, respectively, of water containing gas bubbles with only one size (r=9.94x10 -4 m) and a gas volume fraction φ g =3.77x10 -4 . Also, it is shown that the theory of Commander and Prosperetti (1989) matches the experimental data of Silberman (1957) for the same model conditions. Fig.…”
Section: Comparison With Existing Modelssupporting
confidence: 49%
See 3 more Smart Citations
“…Figures 1 and 8 of Commander and Prosperetti (1989) show the dispersion and phase velocity, respectively, of water containing gas bubbles with only one size (r=9.94x10 -4 m) and a gas volume fraction φ g =3.77x10 -4 . Also, it is shown that the theory of Commander and Prosperetti (1989) matches the experimental data of Silberman (1957) for the same model conditions. Fig.…”
Section: Comparison With Existing Modelssupporting
confidence: 49%
“…All, the low-frequency-limit, the highfrequency-limits and the complicated dispersion behavior in the vicinity of the resonance frequency is almost identical. Also, the data of Silberman (1957) is equally well matched by our model in comparison with the model of Commander and Prosperetti (1989). Attenuation in Commander and Prosperetti (1989) is given in dB/cm, that is, a logarithmic unit with an arbitrary reference value.…”
Section: Comparison With Existing Modelsmentioning
confidence: 84%
See 2 more Smart Citations
“…The bubble size governs the resonance frequency of a bubble, and therefore the bubble size distribution with respect to the main frequency defines the degree of attenuation (Carstensen and Foldy, 1947;Silberman, 1957;Fox et al, 1995). According to Eq.…”
Section: Relevant Errors For Industrial Conditionsmentioning
confidence: 99%